Analysis of Event Implementation in Increasing Parking Revenue at The Plaza Millennium Medan - Parulian, Daniel Dohar; Lubis, Irsad (Universitas Negeri Medan, 2024)
Parking is one of the sources of revenue at The Plaza Millennium. This research aims to determine the impact of event implementation on increasing parking revenue at The Plaza Millennium Medan. The research object is the Total Parking Revenue of The Plaza Millennium, including both car and motorcycle parking, during the period from January to June 2023, as well as the events held at The Plaza Millennium. The implementation of these events broadly consists of four stages: 1) Planning; 2) Execution; 3) Observation; and 4) Reflection. The research was conducted from January to June 2023. Multiple Linear Regression analysis was employed for the research. The results indicate that event implementation has a positive but statistically insignificant effect on the increase in parking revenue at The Plaza Millennium Medan.